2022
DOI: 10.1093/jacamr/dlac038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenem resistance and its potential association with antimicrobial use in humans and animals in rural communities in Vietnam

Abstract: Background Vietnam and Southeast Asia are hotspots for antimicrobial resistance; however, little is known on the prevalence of carriage of carbapenem resistance in non-hospitalized humans and in animals. Carbapenem-resistant Enterobacteriaceae (CRE), particularly Escherichia coli (CREC) and Klebsiella pneumoniae (CRKP) and also Acinetobacter baumannii (CRAB) are emerging threats worldwide. Methods We investigated healthy huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Supporting our findings, a recent study by Yen et al 19 investigating the prevalence of CRE in rural Vietnam identified both bla NDM and bla OXA as the predominant carbapenemase genes. It is worth noting that many studies are conducted in hospital settings, often involving critically ill patients, particularly those in ICUs, or are focused on specific bacterial species.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting our findings, a recent study by Yen et al 19 investigating the prevalence of CRE in rural Vietnam identified both bla NDM and bla OXA as the predominant carbapenemase genes. It is worth noting that many studies are conducted in hospital settings, often involving critically ill patients, particularly those in ICUs, or are focused on specific bacterial species.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to NTS and E. coli (both commensal and pathogenic), other Enterobacteriaceae including Klebsiella spp., and Shigella spp., have been monitored for their AMR profiles in human populations [ 6 ]. Resistance to the last-resort antimicrobial drugs (such as carbapenem and colistin) among Enterobacteriaceae has increased globally, especially in LMICs [ [7] , [8] , [9] ]. Increased resistance among Enterobacteriaceae is partly associated with the overuse of antimicrobials in animal production systems [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…These rates are higher than the rates of 6.6% and 8.5% in 2014 and 2019 studies from China, respectively ( 29 , 30 ), but lower than the rates of 12.2% in Japan ( 31 ) and 37.9% in Iran ( 32 ). Previous studies among non-hospitalized human rectal swabs reported carriage rates of CRE of 0.6% in Vietnam ( 33 ), 0.4% in Spain ( 34 ), and 6.1% in India ( 35 ). However, the prevalence of CRE (10.84%) among hospitalized patients was a much lower than the 13% reported from Vietnam ( 36 ), and higher than the 2.9% rate in Spain ( 34 ).…”
Section: Discussionmentioning
confidence: 97%